REGIONAL ECONOMIC INTEGRATION ON THE NEW SILK ROAD - Ramazanov А.; Krengauz, I.; Karimova, M. (Journal of Oriental Studies, 2023)
The development of integration processes and the enhancement of their role in the world community contributes to the stabilization of the political and economic situation, more efficient use of the natural resource potential, an increase in the level of competitiveness of its actors, and the rating of the states that form the region in the global human development index. Regional interstate integration makes it possible to create a favorable business climate for attracting external investors, prerequisites for the formation of a single economic regional space. As part of the New Silk Road, a radical improvement in infrastructure will significantly revive economic activity in Kazakhstan, accelerate ongoing industrialization, and inject large-scale investments into related projects. Regional interstate integration will also contribute to the improvement and deepening of the international division of labor, encouraging the countries of the Great Silk Road to develop international cooperation, and it is the first preparatory step towards integration. The value of the study (the contribution of this work to the relevant field of knowledge). An attempt was made to develop a system of specific steps to create prerequisites for the development of integration processes within the framework of the New Silk Road. The practical significance of the results of the work. Based on the analysis of traditional and new economic and political factors, trends in the development of regional integration processes, as well as modern threats and risks hindering regional integration, are identified, the main means and directions for their minimization are identified. It is assumed that the implementation of the results of the study will increase the level of competitiveness, both of the region as a whole and of its constituent states, which may be reflected in an increase in their positions in the Global rankings: competitiveness, innovation and human development. Keywords: cooperation, integration, silk road, region, swot-analysis.